2007
DOI: 10.1158/0008-5472.can-06-4006
|View full text |Cite
|
Sign up to set email alerts
|

A Role for the Fas/FasL System in Modulating Genetic Susceptibility to T-Cell Lymphoblastic Lymphomas

Abstract: The Fas/FasL system mediates induced apoptosis of immature thymocytes and peripheral T lymphocytes, but little is known about its implication in genetic susceptibility to T-cell malignancies. In this article, we report that the expression of FasL increases early in all mice after ;-radiation treatments, maintaining such high levels for a long time in mice that resisted tumor induction. However, its expression is practically absent in T-cell lymphoblastic lymphomas. Interestingly, there exist significant differ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…However, Fas and FasL genes have been traditionally considered tumor suppressor genes [18]. This is supported by findings showing functional polymorphisms in Fas and FasL genes between strains of mice with extremely different susceptibilities to certain tumors [19], although the lack of increase in cancer susceptibility shown by lpr or gld mice suggested a secondary role for Fas signaling in cancer. The Fas/FasL system plays a role in tumor immunosurveillance, a tumor suppressor system whereby T cells and NK cells exert tumor cell destruction, firstly through perforin--granzyme release and secondly through apoptosis induction via FasL and TNF-related apoptosis inducing ligand (TRAIL) [20].…”
Section: The Role Of Fas/fasl-mediated Apoptotic Signalingmentioning
confidence: 93%
“…However, Fas and FasL genes have been traditionally considered tumor suppressor genes [18]. This is supported by findings showing functional polymorphisms in Fas and FasL genes between strains of mice with extremely different susceptibilities to certain tumors [19], although the lack of increase in cancer susceptibility shown by lpr or gld mice suggested a secondary role for Fas signaling in cancer. The Fas/FasL system plays a role in tumor immunosurveillance, a tumor suppressor system whereby T cells and NK cells exert tumor cell destruction, firstly through perforin--granzyme release and secondly through apoptosis induction via FasL and TNF-related apoptosis inducing ligand (TRAIL) [20].…”
Section: The Role Of Fas/fasl-mediated Apoptotic Signalingmentioning
confidence: 93%
“…By analyzing congenic mice derived from interspecific consomic strains for chromosome 19, we mapped Tlyr1 to a region of f14 Mb flanked by D19Mit85 and D19Mit13 microsatellite markers. Tlyr1 lies adjacent to another distal RITL susceptibility region (15) and excludes the candidacy of some genes like Pten (16) and Fas (17,18) for which a role in RITL predisposition has been already proposed.…”
Section: Introductionmentioning
confidence: 88%
“…For example, mouse double-positive PD1.6 thymic lymphoma cells (CD4 + CD8 + CD3 + ) undergo thymic epithelial cell-derived glucocorticoid-mediated apoptosis (35), whereas Thy278 cells die by apoptosis on T-cell receptor/CD3 stimulation (27). We have recently shown that the Cd95/Cd95L system mediates induced apoptosis of immature thymocytes and thymic lymphoma cells after exposure to g-irradiation (18).…”
Section: Cd3mentioning
confidence: 99%
“…Using a panel of interspecific chromosome substitution strains between a resistant strain (SEG/Pas) and a susceptible one (C57BL/6J), we have identified a thymus lymphoma resistance locus on chromosome 19 that includes the Fas gene and identified germ-line functional polymorphisms at this gene that are contributing to the genetic risk of developing T-cell lymphoblastic lymphomas [40,41].…”
Section: Mice To Identify Cancer Susceptibility Genes and Protein Biomentioning
confidence: 99%